Rancang Bangun Aplikasi Manajemen Reservasi Restoran - Zahra Humaira Kudadiri (Jurnal Media Infotama, 2025)
The culinary industry faces challenges in efficiently managing restaurant operations, particularly in table reservations and menu ordering. Many restaurants still rely on manual systems, which can lead to record-keeping errors, double booking, and an unsatisfactory customer experience. Therefore, this study aims to develop a desktop-based restaurant reservation management application designed to assist cashiers and restaurant owners in effectively handling table reservations and menu orders.The research method used is the Waterfall software development model, which includes analysis, design, implementation, and testing phases. The system is developed using Java programming language with MySQL as the database for data storage. The main features of the application include table reservation recording, menu ordering, transaction report management, and restricted access for cashiers and restaurant owners to enhance security and operational transparency. The results indicate that the developed application improves the efficiency of reservation and menu ordering management, reduces the risk of record-keeping errors, and ensures more structured operational data. With this system, restaurants can enhance service quality for customers and optimize their business operations.